Experimental analysis of intelligent vehicle monitoring system using Internet of Things (IoT) - Thamaraimanalan, T.; Mohankumar, M.; Dhanasekaran, S.; Anandakumar, H. (EAI Endorsed Transactions on Energy Web, 2021)
Internet of things is an emerging trend and Wireless sensor networks are embedded with IoT to measure various parameters of a vehicle. Measurements and standards of measurements are the most important stages for measuring an object’s size, length, weight etc., Measuring the weight of small objects does not need much time and efforts, but on the other hand weighing large objects needs lots of time and efforts. A new approach is proposed to monitor the location of the vehicle, engine temperature, tyre pressure, oil level, speed control and load measurement of a vehicle. Even if the device is offline, the logs will be stored in the memory card and it can be used for future analysis. In addition to this theft control is introduced for the security of the vehicle. CC3200 microcontroller is connected with load cell to monitor the total weight of the vehicle and engine temperature is monitored using the temperature sensor. By GPS the location and speed of the vehicle is monitored periodically and the location is uploaded in the cloud environment. Vehicle monitoring with load calculation, anti-theft control and the data acquisition from various sensors incorporated with the Electronic Control Unit (ECU) is collected and processed in the cloud. The proposed framework is effectively adaptable at low cost.
Keywords: Data acquisition; Internet of Things (IoT); Vehicle monitoring system